CHRONOTHERAPY OF NOCTURNAL ASTHMA AND RECENT PATENTS: A REVIEW - imanyu Rai Sharma 1Binu Sharma1, Prabhjot Singh Bajwa1*, Jaya Sharma 2, A nurag Bhargava 1, Shailesh Sharma 3, Abh (Journal of Biomedical and Pharmaceutical Research, 2017)
The study of biological rhythms is called chronobiology. Many diseases have been found to show rhythm in their symptoms and severity. To treat such diseases the timing of drug administration is matched with circadian rhythms of the disease and such treatment is called chronotherapy.Asthma is one of the many diseases showing rhythmicity in its symptoms. Night time worsening of asthma has been reported in literature from early times. For the effective management of asthma patient needs to take medicine so that effective concentration of the drug is maintained throughout the night especially during early morning hours.Chronotherapy of asthma has been done using various drugs which include β2-adrenergic agonist medication such as short acting β2-adrenergic agonist (SABA) and long acting β2-adrenergic agonist (LABA). Terbutaline sustained release tablet formulation was one of the first to be assessed in chronotherapy trials. Other drugs to be studied for chronotherapy are theophylline, prednisolone (Systemic corticosteroids), Tiotropium (anticholinergic agent), Montelukast, Pranlukast, and Zafirlukast (leukotriene receptor antagonists). Chronotherapy of nocturnal asthma has shown promising results but right dosing and timing is necessary to yield such results.  Chronotherapeutic drug delivery systems are formulated to achieve the right time delivery of the drugs to match biological rhythms of the disease. Different formulation strategies are followed to achieve such delivery.Present review outlines the basics of chronotherapy along with chronotherapy of Nocturnal asthma and patents granted for chronotherapeutic drug delivery systems for asthma.Keywords: Nocturnal asthma; chronotherapy; circadian; chronotherapeutic